Development of Urban Driving Cycle for Hilly Urban Area for Composite Analysis of Electric Vehicles in Islamabad - Ali Hussain Umar Bhatti (00000274559); Dr Ghulam Ali (USPCAS-E, NUST, Islamabad, 2021)
TH-302
Keywords: MS-ESE Thesis